EFFECTIVE COMMUNICATION PRINCIPLES IN THE QURAN: FOSTERING HARMONIOUS INTERPERSONAL RELATIONSHIP - Surasman, Otong; Ganiem, Leila Mona (Bajang Institute, 2024)
This study aims to identify the principles of effective communication found in the Quran and evaluate their application in daily life to build harmonious interpersonal relationships. While extensive research has been conducted on effective communication, studies specifically examining Quranic communication principles and their practical implementation remain limited. The Quran, as the holy book of Islam, not only provides spiritual guidance but also offers communication principles that can address contemporary communication challenges. This study uses a qualitative approach to explore these principles. Primary data is derived from Quranic verses related to communication, while secondary data includes Quranic tafsirs, books on Islamic communication, and academic articles on effective communication theories. Text analysis is conducted to categorize verses based on themes such as honesty (qaulan sadidan), kindness (qaulan ma’rufan), wisdom (qaulan balighan), empathy and compassion (qaulan layyinan), and respect (qaulan kariman). The findings reveal that Quranic communication forms align closely with the effective communication theories of Stewart L. Tubbs and Sylvia Moss, and the interpersonal communication theories of Muhammad Budyatna and Leila Mona Ganiem. These principles emphasize understanding, honesty, clarity, respect, and gentleness, which collectively enhance communication quality and interpersonal relationships. This study provides practical solutions for improving communication in a complex and diverse society, recommending the adoption of Quranic communication forms in daily practices to foster understanding, build trust, and create a harmonious communication environment.